Indications for the HPV vaccine in adolescents: A review of the literature - Soares, Glaucia Resende [UNESP]; Vieira, Ribia da Rocha [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Miyahara, Glauco Issannu [UNESP] (Elsevier B.V., 2015)
Background: The vaccine against human papillomavirus (HPV) was created to abrogate the risk that the virus presents for the development of cervical cancers. The prevalence of HPV infection among healthy individuals is significant (20%). We performed a review of the literature published in the period from 2008 to 2012 regarding the use of the vaccine against HPV specifically in adolescents. Methods: The articles were selected from a search of the PubMed database with the key words "vaccine", "HPV" and "adolescent". This search identified 576 articles; based on readings of the titles and abstracts, the list of included article was reduced to 42. Results: We observed that the majority of authors are in favor of the vaccine for adolescents particularly females. Conclusion: Recommending the use of the HPV vaccine and other vaccines represents an attempt to broaden the reach of these vaccines among both sexes of the adolescent population. Vaccination is a strategy for the prevention of pre-cancerous Lesions in the genital and oropharyngeal regions. (C) 2014 King Saud Bin Abdulaziz University for Health Sciences. Published by Elsevier Limited. All rights reserved.
Keywords: Vaccine; HPV; Adolescent